The Borders Within: When the Right to Non-discrimination Confronts Migration Law - Stoyanova, Vladislava; Atalay, Serde ; 0000-0002-0934-9570; Loxa, Alezini ; 0000-0002-7345-6266 (International Journal of Discrimination and the Law, 2025)
Editorial for the special issue 'The Borders Within: When the Right to Non-discrimination Confronts Migration Law ' (2025) 25(2) International Journal of Discrimination and Law
Keywords: Migration law; EU law; Human rights; Migrationsrätt; EU-rätt; Mänskliga rättigheter